Peningkatan Kesadaran Hukum Masyarakat dalam Interaksi pada Dunia Digital di Kelurahan Banjarsari Kota Surakarta - Broto Laksito, FX Hastowo; Pradoto, Waluyo Slamet; Bawono, Aji (Jurnal SOLMA, 2024)
Background: The development of technology and information is happening very rapidly in the midst of society along with the progress of the times. This then has the potential to result in people's behavior in using gadgets and social media that utilize information technology in a positive or negative direction. The lack of public understanding regarding literacy in digital interaction has an impact on losses in society and even triggers legal problems. The aim is to increase public awareness and understanding of the use of gadgets and social media by utilizing the internet network wisely in order to avoid legal sanctions and provide a more positive impact on its users. Method: Socialization and interactive discussion. The partners invited to collaborate in this community service are Banjarsari Urban Village, especially in Rukun Warga 01, totaling 15 people. Internet and social media usage behavior such as spreading fake news and hatred, defamation, online gambling, pornography, online fraud is increasingly rampant. Results: There is an increase in insight in identifying actions that can be prosecuted by law through the Electronic Information and Transactions Law. Conclusion: The use of social media by the community can be used for more productive and positive activities compared to carrying out activities in cyberspace such as increasing literacy, business, networking rather than negative actions that have the potential to conflict with the law and will harm them.